PKM Melalui Pelatihan Pembuatan Bak Cuci Tangan untuk Pencegahan Penyebaran Covid-19 di Kota Makassar - Nurlita Pertiwi; Nurul Muhlisa Abdal (Universitas Negeri Makassar, 2020)
These Community Partnership Program (PKM) partners are administrators of the Muhajirin Mosque and the Gowa Care Community. The problem faced is the spread of the Covid-19 virus which is increasingly widespread so that efforts need to be made to reduce the level of virus spread. The PRA method is carried out to generate a sense of belonging (sense of belonging) to partners for the products to be developed, and a sense of responsibility (sense of responsibility) of partners towards the products and the environment around them. The main method adopted in this Community Partnership Program (PKM) activity is lectures and hands-on practice. The results achieved were increased public knowledge about the importance of tackling the spread of Covid-19 and increased skills of participants in making hand sinks placed in traditional markets